Inflation-linked Bonds: An Introduction - Maria Farrugia; Glenn Formosa; Joseph Julian Pace (Central Bank of Malta, 2018)
This paper gives an overview of inflation-linked bonds (ILBs). In the first part, it describes the characteristics of inflation-linked bonds and their pricing mechanics. This is followed by an illustrative example which compares the cashflow structure of the two types of fixed income securities. An analysis of the historical performance of inflation-linked bonds relative to their nominal counterparts1 follows on the basis of the Bloomberg Barclays total return indices for the US and Germany. Correlations between ILBs and fixed coupon bonds were computed.
Keywords: D53; E44; G1; 330